Longitudinal transcriptomic analysis of mouse sciatic nerve reveals pathways associated with age‐related muscle pathology - Nicole Comfort; Meethila Gade; Madeleine Strait; Samantha J. Merwin; Daphne Antoniou; Chiara Parodi; Lina Marcinczyk; Lea Jean‐Francois; Tessa R. Bloomquist; Anna Memou; Hardy J. Rideout; Stefania Corti; et al. (Wiley, 2023)
Abstract Background Sarcopenia, the age‐associated decline in skeletal muscle mass and strength, has long been considered a disease of muscle only, but accumulating evidence suggests that sarcopenia could originate from the neural components controlling muscles. To identify early molecular changes in nerves that may drive sarcopenia initiation, we performed a longitudinal transcriptomic analysis of the sciatic nerve, which governs lower limb muscles, in aging mice. Methods Sciatic nerve and gastrocnemius muscle were obtained from female C57BL/6JN mice aged 5, 18, 21 and 24 months old (n = 6 per age group). Sciatic nerve RNA was extracted and underwent RNA sequencing (RNA‐seq). Differentially expressed genes (DEGs) were validated using quantitative reverse transcription PCR (qRT‐PCR). Functional enrichment analysis of clusters of genes associated with patterns of gene expression across age groups (adjusted P‐value < 0.05, likelihood ratio test [LRT]) was performed. Pathological skeletal muscle aging was confirmed between 21 and 24 months by a combination of molecular and pathological biomarkers. Myofiber denervation was confirmed with qRT‐PCR of Chrnd, Chrng, Myog, Runx1 and Gadd45ɑ in gastrocnemius muscle. Changes in muscle mass, cross‐sectional myofiber size and percentage of fibres with centralized nuclei were analysed in a separate cohort of mice from the same colony (n = 4-6 per age group). Results We detected 51 significant DEGs in sciatic nerve of 18‐month‐old mice compared with 5‐month‐old mice (absolute value of fold change > 2; false discovery rate [FDR] < 0.05). Up‐regulated DEGs included Dbp (log2 fold change [LFC] = 2.63, FDR < 0.001) and Lmod2 (LFC = 7.52, FDR = 0.001). Down‐regulated DEGs included Cdh6 (LFC = −21.38, FDR < 0.001) and Gbp1 (LFC = −21.78, FDR < 0.001). We validated RNA‐seq findings with qRT‐PCR of various up‐ and down‐regulated genes including Dbp and Cdh6. Up‐regulated genes (FDR < 0.1) were associated with the AMP‐activated protein kinase signalling pathway (FDR = 0.02) and circadian rhythm (FDR = 0.02), whereas down‐regulated DEGs were associated with biosynthesis and metabolic pathways (FDR < 0.05). We identified seven significant clusters of genes (FDR < 0.05, LRT) with similar expression patterns across groups. Functional enrichment analysis of these clusters revealed biological processes that may be implicated in age‐related changes in skeletal muscles and/or sarcopenia initiation including extracellular matrix organization and an immune response (FDR < 0.05). Conclusions Gene expression changes in mouse peripheral nerve were detected prior to disturbances in myofiber innervation and sarcopenia onset. These early molecular changes we report shed a new light on biological processes that may be implicated in sarcopenia initiation and pathogenesis. Future studies are warranted to confirm the disease modifying and/or biomarker potential of the key changes we report here.